Foreign language communicative culture formation continuity in school-vocational school-university system - E.M. Vildanova, E.V. Salimullina, M.S. Ilina, (Opción, 2019)
The study aims to investigate the foreign language communicative culture formation continuity in school-vocational school-university system via pedagogical experiment, observation, conversation, survey, modeling, method of expert evaluations and method of mathematical statistics. As a result, vocabulary is sufficient for interpersonal communication in situations close to professional and intercultural interaction. In conclusion, the influence of individual pedagogical techniques varies depending on the goals and objectives of each stage of communicative culture formation at the English lessons